Strategies for poverty reduction - Easter, Christopher ed. (Commonwealth Secretariat LondonGB, 1993)
Focuses on direct, poverty-specific measures to mitigate the present hardships faced by the poor. Sees the reduction of poverty as a central objective of national policies and programmes. Perceives rural, agriculture-led growth as a successful and appropriate strategy for most countries to follow.